2013
DOI: 10.1002/2013eo470001
|View full text |Cite
|
Sign up to set email alerts
|

Smartphones: Powerful Tools for Geoscience Education

Abstract: Observation, formation of explanatory hypotheses, and testing of ideas together form the basic pillars of much science. Consequently, science education has often focused on the presentation of facts and theories to teach concepts. To a great degree, libraries and universities have been the historical repositories of scientific information, often restricting access to a small segment of society and severely limiting broad‐scale geoscience education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…National Higher Education ICT Initiative 2007; Perlmutter, 2011;PIALP, 2013). Closing the gap can only lead to more engaging and meaningful educational experiences as undergraduate students and the general public are more and more attached to mobile devices (Dahlstrom et al, 2011;Johnson & Johnston, 2013;PIALP, 2013).…”
Section: Utilizing Smartphones Instead Of Banning Them-gaming In Undementioning
confidence: 99%
See 3 more Smart Citations
“…National Higher Education ICT Initiative 2007; Perlmutter, 2011;PIALP, 2013). Closing the gap can only lead to more engaging and meaningful educational experiences as undergraduate students and the general public are more and more attached to mobile devices (Dahlstrom et al, 2011;Johnson & Johnston, 2013;PIALP, 2013).…”
Section: Utilizing Smartphones Instead Of Banning Them-gaming In Undementioning
confidence: 99%
“…Smart devices are also used in community and classroom data-collection exercises through basic apps that leverage the use of their various built-in sensors. Examples include the iSeismometer that makes use of the iPhone's GPS and accelerometer to illustrate how seismic data is collected and the Theodolite app that makes use of the internal compass, inclinometer and GPS tools (Johnson & Johnston, 2013).…”
Section: Utilizing Smartphones Instead Of Banning Them-gaming In Undementioning
confidence: 99%
See 2 more Smart Citations
“…The experiential gaming model includes idea generation, experiences, and challenges that generate new ideas (Kiili, 2005). Although on one hand, mobile AR technologies can represent a communication gap between incoming freshmen and educators (National Higher Education ICT Initiative, 2007;Perlmutter, 2011;Dahlstrom and Bichsel, 2014), studies have shown that simulations, games, and virtual field trips (VFTs) actually increase students' motivation (McGreen and Sánchez, 2005;Bell et al, 2009;Honey and Hilton, 2011;Johnson and Johnston, 2013;Bursztyn et al, 2017). There have been increasing reports of VFTs being used in a variety of college courses, including biology, medicine, engineering, geography, and geology (e.g., Spicer and Stratford, 2001;Liarokapis et al, 2004;Stumpf et al, 2008;Jacobson et al, 2009;Yuen et al, 2011;Lee, 2012;Pringle, 2013;Friess et al, 2016).…”
Section: Introductionmentioning
confidence: 99%